1994
DOI: 10.1002/maco.19940451202
|View full text |Cite
|
Sign up to set email alerts
|

Korrosionsinhibierung bzw. ‐stimulation von Aluminiumpigmenten im alkalisch wäßrigen Medium durch Polyacrylsäuren

Abstract: Blattchenformige Aluminiumpigmente (Aluminiumgehalt > 99.5%) werden in einem (iemisch aus Wasser und Butylglykol bei pH = 10 schncll unter Wasserstoffentwicklung korrodiert. Niedrigmolekulare Polyacrylsauren inhibieren bei einem Zusatz von 0,3-0.5 Gew.-oh die Korrosion von Aluminiumpigmentcn deutlich bcsscr als hochmolekulare. Bei sehr niedrigen Zusatzmcngen (0.05-0,l Gcw.-%) von Polyacrylsauren zeigen die niedrigmolekularen keine Wirkung, wahrend hochmolckulare die Korrosion stimulieren. D.h. hochmolekulare P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1996
1996
2015
2015

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…Reviews of the literature on the anodic behaviour of tin electrode in acidic media showed that the most of the work has been done in carboxylic and the so called fruit acids [17][18][19][20]. Only very little work is available on the influence of isobutyric acid on the electrochemical behaviour of tin.…”
Section: Introductionmentioning
confidence: 99%
“…Reviews of the literature on the anodic behaviour of tin electrode in acidic media showed that the most of the work has been done in carboxylic and the so called fruit acids [17][18][19][20]. Only very little work is available on the influence of isobutyric acid on the electrochemical behaviour of tin.…”
Section: Introductionmentioning
confidence: 99%